2020
DOI: 10.1261/rna.076562.120
|View full text |Cite
|
Sign up to set email alerts
|

Ribo-Pop: simple, cost-effective, and widely applicable ribosomal RNA depletion

Abstract: The measurement of RNA abundance derived from massively parallel sequencing experiments is an essential technique. Methods that reduce ribosomal RNA levels are usually required prior to sequencing library construction because ribosomal RNA typically comprises the vast majority of a total RNA sample. For some experiments, ribosomal RNA depletion is favored over poly(A) selection because it offers a more inclusive representation of the transcriptome. However, methods to deplete ribosomal RNA are generally propri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Systematic RNA-seq data comparison indicated that RNA-seq from rProbe libraries yielded a highly correlative transcriptomic landscape with that of the commonly used Illumina Ribo-Zero Kit and poly(A) selection method. However, about 3% of genes showed significant expression changes between rProbe and poly(A) selection method, as same as the disturbance have been reported (Morlan et al 2012 ; Zhao et al 2018 ; Thompson et al 2020 ). Culture condition and library preparation that makes the RNA pool differ in concentration and composition might be one of the explanations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Systematic RNA-seq data comparison indicated that RNA-seq from rProbe libraries yielded a highly correlative transcriptomic landscape with that of the commonly used Illumina Ribo-Zero Kit and poly(A) selection method. However, about 3% of genes showed significant expression changes between rProbe and poly(A) selection method, as same as the disturbance have been reported (Morlan et al 2012 ; Zhao et al 2018 ; Thompson et al 2020 ). Culture condition and library preparation that makes the RNA pool differ in concentration and composition might be one of the explanations.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, numerous rRNA-depletion methods have been developed including commercial kits such as Ribo-Zero Gold rRNA Removal Kit (Yeast), which has not yet launched new alternatives for fungi after discontinued. Several studies have reported the species-specific RNA-seq library construction methods that use hybrid-subtraction strategies for rRNA removal in higher eukaryotes and bacteria (Giannoukos et al 2012 ; Thompson et al 2020 ; Zeng et al 2020 ). Recently, a similar method has also been reported in Cryptococcus neoformans (Telzrow et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter approach, DNA oligos complementary to rRNA facilitate their removal prior to library construction. These oligos can be biotinylated for magnetic bead affinity purification ( 6 , 22 , 23 ), commercialized for some taxa in the Ribo-Minus and the now discontinued Ribo-Zero Gold kits.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were then pooled and purified over a Zymo Oligo Clean & Concentrator column (Genesee Scientific #11-380) according to manufacturer’s instructions. rRNA was subsequently depleted as previously described ( Thompson et al, 2020 ) using biotinylated oligos oSB6755-oSB6769. rRNA-depleted samples were then reverse transcribed in 20 uL reactions with primer NI802 and Protoscript II (200 U/μl) for 30 min at 50°C.…”
Section: Methodsmentioning
confidence: 99%